(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The present research aims at taking notice about the relationship between psychological resilience and self satisfaction on the Damascus University students , and the indication of the differences on the members of the research sample on the scale of Psychological resilience and its relation regarding the two research variables (Gender, specialty or position).The researcher depended on the descriptive analytical approach . The research sample also consisted of (500) students males and females: and the researcher applied the self resilience scale (2012) and the scale of life satisfaction prepared by Magdy Al-Desogy (1988), where the following law and statistical methods were involved :The numerical averages , the PERSON interrelation coefficient , the coefficient of SPERMAN BROWN , the coefficient of ALPHA CROMBAGE , and the research conclusionreached at the following results: 1. The presence of an interconnection of a statistical indication between psychological resilience and life satisfaction at the members of the Damascus University students sample. 2. The presence of differences of statistical indication between the average of grades of the research sample on the psychological resilience regarding the gender variable in favor of male students. 3. The absence of differences of statistical indication between the average grades of the research sample members on the scale of psychological resilience scale regarding the specialty variable. 4. The presence of differences of statistical indication between the average grades of the research sample on the scale of life satisfaction regarding the variable of gender in favor of male students. 5. The absence of differences of statistical indication between the average grades of the research sample on the scale of life satisfaction regarding the specialty variable.